Estudo das consoantes róticas nas Cantigas de Santa Maria - Barreto, Débora Aparecida dos Reis Justo [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This research studies Archaic Portuguese phonological phenomena, analyzing the rhotic consonants ( and ) present in the first 100 Cantigas de Santa Maria. Rhotic consonants were chosen as main subject because constitute an interesting theme to compose a mosaic of the Portuguese Phonology in the troubadour's period, since there are considerable doubts about their phonological status at that time. The aim of this research is to analyze segmental aspects of troubadour's Archaic Portuguese, more specifically the questions relating to the rhotics in initial and syllable ending positions, graphically represented by or . We also aim to check whether, in that period, there were two rhotic phonemes in opposition (the tap // and multiple vibrant /r/), or if in the phonological level could be considered a geminate variant of . The corpus is selected from Mettman's edition (1986) for the Cantigas de Santa Maria, songbook in praise of the Virgin Mary prepared in the second half of the thirteenth century, which had its authorship attributed to the King of Leon and Castile, Don Alfonso X the Wise. The methodology used in this project was based in the observation of the possibility (or not) of spelling variation in the representation of or and in the checking of the possibility (or not) of rhyme between these words in order to determine which was the phonetic realization in that time. Our results indicate the possibility of the existence of only one rhotic phoneme in Archaic Portuguese (thirteenth century), which could have two variants, one simple and one geminate

A presente pesquisa estuda fenômenos fonológicos do Português Arcaico, analisando especificamente as consoantes róticas ( e ) presentes nas 100 primeiras Cantigas de Santa Maria. Escolheu-se trabalhar com as róticas, pois elas constituem um tema interessante à composição de um mosaico da Fonologia do português na época dos trovadores. O objetivo da pesquisa é analisar os aspectos segmentais do Português Arcaico trovadoresco, mais especificamente as questões relativas às róticas em posição de início e de travamento silábicos, representadas na escrita por ou . Objetiva-se verificar também se, naquela época, havia dois fonemas róticos em oposição (o tepe // e a vibrante múltipla /r/), ou se, no nível fonológico, poderia ser considerada uma variante geminada de . Na pesquisa desenvolvida, o material selecionado para análise foi a edição de Mettmann (1986) das Cantigas de Santa Maria, cancioneiro em louvor da Virgem Maria elaborado na segunda metade do século XIII, que teve sua autoria atribuída ao Rei de Leão e Castela, Dom Afonso X, o Sábio. A metodologia empregada no projeto em questão baseia-se na observação da possibilidade (ou não) de variação da grafia na representação de ou e na verificação da possibilidade (ou não) de rima entre essas palavras, para que, desta forma, se possa determinar como era sua realização fonética naquela época. Os resultados alcançados indiciam a possibilidade da existência de apenas um fonema rótico na época do Português Arcaico (século XIII), que teria duas variantes, uma simples e uma geminada
Keywords: Fonologia; Língua portuguesa - Português arcaico - Até 1400; Lingua portuguesa - Gramatica; Phonology